2007
DOI: 10.1128/jb.01170-06
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Component Regulatory System TCS08 Is Involved in Cellobiose Metabolism ofStreptococcus pneumoniaeR6

Abstract: The two-component system TCS08 is one of the regulatory systems that is important for virulence of Streptococcus pneumoniae. In order to investigate the TCS08 regulon, we have analyzed transcription profiles of mutants derived from S. pneumoniae R6 by microarray analysis. Since deletion mutants are often without a significant phenotype, we constructed a mutation in the histidine kinase HK08, T133P, in analogy to the phosphatase mutation T230P in the H box of the S. pneumoniae CiaH kinase described recently (D.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
74
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 46 publications
8
74
0
Order By: Relevance
“…Apparent homologues of Smu1452 have been found in Streptococcus pneumoniae R6 and Streptococcus gordonii, and in both cases, they are part of a well-conserved cellobiose operon (http://www .oralgen.lanl.gov/). Consistent with our finding, the homologue of Smu1452 in S. pneumoniae appears necessary for cellobiose utilization (20). We are currently exploring the potential role of this hypothetical protein in carbohydrate transport and catabolism by S. mutans.…”
Section: Discussionsupporting
confidence: 70%
“…Apparent homologues of Smu1452 have been found in Streptococcus pneumoniae R6 and Streptococcus gordonii, and in both cases, they are part of a well-conserved cellobiose operon (http://www .oralgen.lanl.gov/). Consistent with our finding, the homologue of Smu1452 in S. pneumoniae appears necessary for cellobiose utilization (20). We are currently exploring the potential role of this hypothetical protein in carbohydrate transport and catabolism by S. mutans.…”
Section: Discussionsupporting
confidence: 70%
“…Examination of cbpA mRNA levels in an in-frame deletion mutant with deletions in both hk06 and rr06 in D39 showed that this mutant produced cbpA mRNA levels similar to the wild-type levels. This is perhaps not surprising in light of a recent study of S. pneumoniae which showed that a deletion mutant with a mutation in either RR08 or the whole TCS08 resulted in no alteration of the mRNA expression profile, whereas an activating HK08 mutation did alter the profile (22). This suggests that loss-of-function TCSTS mutations do not always influence the expression of regulated genes.…”
Section: Discussionmentioning
confidence: 69%
“…Although the mechanism is unclear, there are many precedents. For example, the inactivation of the sensor kinase of the TCS08 TCS of Streptococcus pneumoniae leads to the down-regulation of the genes involved with cellobiose utilization, but the inactivation of the cognate response regulator has no effect (34). Similarly, the inactivation of the CiaR response regulator of S. mutans has little effect on mutacin I production, whereas the inactivation of CiaH, the cognate sensor kinase, abolishes mutacin I production (39).…”
Section: Discussionmentioning
confidence: 99%